Diapiric ascent of silicic magma beneath the Bolivian Altiplano. Issue 10 (31st May 2013) - del Potro, Rodrigo; Díez, Mikel; Blundy, Jon; Camacho, Antonio G.; Gottsmann, Joachim
Abstract: [1] The vertical transport of large volumes of silicic magma, which drives volcanic eruptions and the long‐term compositional evolution of the continental crust, is a highly debated problem. In recent years, dyking has been favored as the main ascent mechanism, but the structural connection between a distributed configuration of melt‐filled pores in the source region and shallow magma reservoirs remains unsolved. In the Central Andes, inversion of a new high‐resolution Bouguer anomaly data over the Altiplano‐Puna Magma Body (APMB) reveals ~15 km wide, vertically elongated, low‐density, 3D structures rooted at the top of the APMB at 20 km depth. We integrate our gravity inversion with the available geophysical, geological, and petrological observations, and in agreement with petrological/mechanical considerations propose that, in this region of the Andes, partially molten granitic bodies ascend diapirically through the hot ductile mid‐upper crust. Key Points: Gravity survey over shallow‐crustal, magmatic structures in a flare‐up setting Low‐density partially molten structures massively rooted at source Diapiric ascent of granitic magmas in a region of thickened continental crust